If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = 8(5n + -2) Reorder the terms: -15 = 8(-2 + 5n) -15 = (-2 * 8 + 5n * 8) -15 = (-16 + 40n) Solving -15 = -16 + 40n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-40n' to each side of the equation. -15 + -40n = -16 + 40n + -40n Combine like terms: 40n + -40n = 0 -15 + -40n = -16 + 0 -15 + -40n = -16 Add '15' to each side of the equation. -15 + 15 + -40n = -16 + 15 Combine like terms: -15 + 15 = 0 0 + -40n = -16 + 15 -40n = -16 + 15 Combine like terms: -16 + 15 = -1 -40n = -1 Divide each side by '-40'. n = 0.025 Simplifying n = 0.025
| 6(9+5v)=-19 | | 20=0.16x-1.28y | | X=-5.75 | | y=500+0.5y | | 6(7d-3)=-29 | | .50+0.5x=2.50 | | 72=3x+14 | | 9k+2=3k-22 | | 4ab+3ba= | | 8x-2(x+4)=10 | | 0=-16t^2+41t+209 | | ln(3x)=3ln(x) | | 345(x+75)=45 | | 2x=3+-0.5y | | 9j-7+3j=6j-10j+3j | | .25+0.5x=2.25 | | -5(-3x+2)-2=2 | | 6k+2=2k-14 | | -5(-3x+2)-2=-2 | | -7x+4=-6x+1 | | 5(2x+4)-3=3 | | 49x-20x-10=0 | | (3x-4)+2=1 | | 2x=-6+-12 | | 2(x+4+3)=6 | | 6+-12=6 | | -5m+6=-8m+3(-8-4m) | | 6(1+5y)=(m-2) | | -3(x-3)+3=6 | | 6x-10+3x=0 | | -8(-x-6)+10=-2 | | 1208-41x=14x+53 |